The Effect of Using Interactive Simulation (Phet) and Virtual Laboratories (Praxilabs) on Tenth-Grade Students’ Achievement in Physics - Ashraf Ali Bani Yassin (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The study aimed at investigating the impact of physics education using the interactive simulation program (PHET) and the virtual laboratories (Praxilabs) on the achievement of the tenth core class students in the Northern Mazar district of education. The study sample consisted of (105) students from the tenth core class of the Irhaba Secondary School for Boys, divided into three simple randomness groups, the first group and the second experimental group and the third group officer. The first experimental group consisted of (32) students who studied using the interactive simulation program (PHET). The second experimental group consisted of (41) students who studied using virtual laboratories (Praxilabs). The third group consisted of (32) students who studied using the standard method. The study tool consisted of a collection test designed by the researcher. The results of the study showed statistically significant differences between the average performance of the students in the two experimental groups and the performance of the RDT for the two experimental groups. The study also showed that there is a statistically significant difference between the average performance of the first experimental group and the second group for the second experimental group, which was studied using the virtual laboratories (PraxiLabs). The study recommended that private physics teachers and general science teachers should use virtual laboratories (PraxiLabs) and PHET in the educational process.